Twenty-two years of SDI research in Kansas - Lamm, Freddie R., author; Rogers, Danny H., author; Alam, Mahbub, author; O'Brien, Daniel M., author; Trooien, Todd P., author (Colorado State University. Libraries, 2011)
This paper will summarize research efforts with subsurface drip irrigation in Kansas that has occurred during the period 1989 through 2010. Special emphasis will be made on brief summaries of the different types of research that have been conducted including water and nutrient management for the principal crops of the region, SDI design parameters and system longevity and economics. Annual system performance evaluations have shown that dripline flowrates are within 5% of their original values. Economic analysis shows that systems with such longevity can be cost competitive even for the lower-valued commodity crops grown in the region.
Proceedings of the 23rd annual Central Plains irrigation conference
Presented at Proceedings of the 23rd annual Central Plains irrigation conference held in Burlington, Colorado on February 22-23, 2011.